50 business classics : your shortcut to the most important ideas on innovation, management, and strategy - Butler-Bowdon, Tom, 1967- (London ; Boston : Nicholas Brealey Publishing, 2018)
"Discover how to make more money and make it work for you- and find out how creating wealth can lead to fulfilling your personal potential and gaining peace of mind. 50 prosperity classics provides a unique overview of the landmark titles on wealth creation and abundance"-- Back cover.
"The greatest books distilled"--Cover.
Includes bibliographical references.
Keywords: Industrial management -- Bibliography; Entrepreneurship -- Bibliography; Money -- Psychological aspects -- Bibliography; Wealth -- Psychological aspects -- Bibliography; Millionaires -- Psychology -- Bibliography; Capitalists and financiers -- Psychology -- Bibliography; Humanitarianism -- Bibliography; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Mentoring & Coaching; Capitalists and financiers -- Psychology; Entrepreneurship; Humanitarianism; Industrial management; Millionaires -- Psychology; Money -- Psychological aspects; Wealth -- Psychological aspects; Bibliography